Isu-Isu Global Transformasi, Inovasi Dan Difusi Pendidikan World Class Education Studi Kasus Di Man Insan Cendekia Serpong - Yumesri, Yumesri; Latif, Mukhtar; Us, Kasful Anwar; Sudur, Sudur (Innovative: Journal Of Social Science Research, 2024)
The process of educational innovation is seen when there are still continuous changes until the process is declared over. The time needed for each individual or organization in the innovation process varies depending on the individual or organization's readiness to respond to the innovation. The changes in the impact of disruption have penetrated all aspects of life, including education. In the current era of globalization, the main challenge for educational institutions is to remain relevant and adaptive to rapid changes at the global level. Education in Indonesia, especially Islamic education, faces demands to not only produce students who are academically competent, but also have sensitivity to universal values ​​and the ability to adapt to global changes. MAN Insan Cendekia Serpong as one of the leading educational institutions that applies the concept of world-class education is a relevant example to study. In the context of Islamic education, the integration of religious values ​​with general education and the application of technology and innovation in learning